Spatiotemporal variability of dairy manure temperature during storage in earthen pits: Associations with meteorological factors - Rana A. Genedy; Jactone A. Ogejo (PLoS ONE, 2026)
Manure storage is a critical component of nutrient management in dairy systems, but it is also a major source of greenhouse gas emissions and nutrient losses. Temperature regulates microbial activity and associated emissions; however, its spatial and temporal dynamics within stored manure are not well characterized. This study characterized the temporal and spatial variability of manure temperature in a dairy manure storage pit and examined its relationships with meteorological factors and management practices. Temperature was monitored at multiple vertical locations within the manure column over seasonal cycles, and statistical and machine-learning analyses were used to identify key drivers. Manure temperature exhibited clear seasonal patterns and vertical stratification, with differences of up to 10°C observed between lower and upper manure layers. During colder periods, higher temperatures were consistently observed in lower manure layers, whereas during warmer periods, temperatures near the surface sometimes approached or exceeded ambient air temperature. Temperature gradients are periodically reversed, producing turnover events that redistribute heat within the manure column, even in the presence of a surface crust. Ambient air temperature was the dominant external driver, explaining a substantial proportion of variability in manure temperature (R² = 0.72–0.84), while manure volume moderated the influence of atmospheric variability on internal temperatures. Other meteorological variables had comparatively smaller effects. These findings demonstrate that stored manure behaves as a vertically stratified thermal system governed by the interaction of atmospheric forcing and internal heat generation. Incorporating spatially resolved manure temperature dynamics into emission models can improve predictions of environmental impacts and inform more effective manure management strategies.